2019
DOI: 10.31782/ijcrr.2019.11213
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Infections and Aflatoxin Contamination in Maize Grains Collected from West Showa and East Wallega Zones, Ethiopia

Abstract: Mycotoxin affects the world's food crops and creates a large economical loss in the developed and developing countries. Aflatoxins are a group of mycotoxins that mainly produced by Aspergillus species viz., A. flavus, and A. parasiticus. An aflatoxins contamination of maize grains has exhibiting a serious threat to human and animal health over the past two decades. Toprotect the safety of food commodities, regular monitoring and diagnosis of the presence and amount of non-permissible levels of aflatoxins in fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…In contrast, the sample containing more color had lower aflatoxin concentration. In the present study the samples collected from NGAFS7, MLAFS18 showed the aflatoxin concentration of 521.67±2.08 μg/kg, 524.33±4.04 μg/kg, was toxic when compared to other samples, this could be due to the exposure of the grain to favorable temperature and rain which in turn facilitate the growth of aflatoxigenic fungi [ 16 ]. The Aflatoxin concentration of the samples collected from NGAFS3, MYAFS14, MLAFS20, MLAFS21, CHAFS26, CHAFS27 was found to be 315.67±2.51 μg/kg, 308.00±2.64 μg/kg, 313.67±2.51 μg/kg, 319.33±2.08 μg/kg, 315.67±2.51 μg/kg, 310.67±1.52 μg/kg respectively indicates moderately toxic.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast, the sample containing more color had lower aflatoxin concentration. In the present study the samples collected from NGAFS7, MLAFS18 showed the aflatoxin concentration of 521.67±2.08 μg/kg, 524.33±4.04 μg/kg, was toxic when compared to other samples, this could be due to the exposure of the grain to favorable temperature and rain which in turn facilitate the growth of aflatoxigenic fungi [ 16 ]. The Aflatoxin concentration of the samples collected from NGAFS3, MYAFS14, MLAFS20, MLAFS21, CHAFS26, CHAFS27 was found to be 315.67±2.51 μg/kg, 308.00±2.64 μg/kg, 313.67±2.51 μg/kg, 319.33±2.08 μg/kg, 315.67±2.51 μg/kg, 310.67±1.52 μg/kg respectively indicates moderately toxic.…”
Section: Resultsmentioning
confidence: 96%
“…ELISA reader was employed for the quantification of aflatoxin B1. Finally, detected and quantified aflatoxin B1 was used for analysis across each sample, grain and storage types [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, [ 55 ] reported total fumonisin levels of 25 to 4500 μg/kg in maize samples collected from 20 major maize-growing areas in the country, of which about 7% of the maize samples exceeded the maximum tolerable limit set by the EU in maize (>1000 μg/kg) [ 36 ] and surpassed the levels of fumonisin in the present study detected in sorghum grain. In addition, aflatoxin B 1 was detected in the range of 3.9 to 382 μg/kg in maize grain samples [ 56 ], in which 7.7% of samples had aflatoxin B 1 content higher than the maximum limit (5 μg/kg) set by EU in maize to be used as an ingredient in foodstuffs [ 56 ]. Recently, [ 57 ] detected about 23 metabolites in maize grain samples collected from south and south-west of Ethiopia and reported nivalenol (1052 μg/kg), deoxynivalenol (2158 μg/kg), zearalenone (2447 μg/kg), fumonisin B 2 (2712 μg/kg), and fumonisin B 1 (7069 μg/kg) were abundantly detected.…”
Section: Resultsmentioning
confidence: 99%
“…In this model, we also control for the estimated macronutrient and micronutrient content and pathogens (vector Civ` ) in the milk sample collected at the baseline from the household in which the child resides. We will also control for the child’s maize consumption (vector Hiv` ), since maize is also likely to be contaminated by aflatoxins in the Ethiopian setting 34–37. The estimated model can be defined as:…”
Section: Discussionmentioning
confidence: 99%